Analysis and Experimental Study on Bearing Capacity of “All-Inclusive” Underpinning Joint - Kefeng Yue; Lei Yan (Advances in Civil Engineering)
Aiming at the phenomenon of punching failure and large slip at the new-to-old concrete interface of “beam-column” underpinning joint, a new type of “all-inclusive” underpinning joint is tested and numerically analyzed, which adopts the spraying glue + grooving + planting bars + prestressed + hooping connection method. The experimental and numerical analysis results show that the connection method of “all-inclusive” underpinning joint can effectively avoid punching failure of the joint, and the failure mode is mainly flexure-shear. Then, the “all-inclusive” underpinning joint can delay the initial slip at the new-to-old concrete interface and reduce the overall slip. Finally, combining the theoretical and experimental results, a simplified calculation formula for the bearing capacity of the “all-inclusive” underpinning joint is improved. The theoretical results are in good agreement with the experimental results, which indicates that the calculation of the bearing capacity of the underpinning joint using the formula in this paper is feasible and can provide experimental and theoretical references for similar projects.